(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and laboratory characteristics of Gram-negative neonatal infections and to identify risk factors associated with multidrug-resistant (MDR) Gram-negative infections at the Pediatric Center, Bach Mai Hospital, during 2023–2025. Methods: A cross-sectional study combined with a case–control design was conducted among neonates (<28 days old) diagnosed with neonatal sepsis. The case group included 60 infants with culture-confirmed MDR Gram-negative infections, and the control group consisted of 180 infants with negative cultures. Clinical manifestations, laboratory findings, and potential risk factors were collected and statistically analyzed. Results: Among 60 cases of Gram-negative neonatal infections, late-onset sepsis accounted for 78.9%, while early-onset sepsis accounted for 21.1%. Klebsiella pneumoniae was the most common pathogen (42.3%). The predominant clinical features were respiratory distress (83.3%), tachypnea ≥60 breaths/min (75%), chest retraction (73.3%), SpO₂ <90% (56.7%), poor feeding (56.7%), and jaundice (35%). Laboratory abnormalities included leukocytosis (43.3%), thrombocytopenia (40%), hypoalbuminemia (66.7%), elevated CRP (78.3%), and coagulopathy(70%). Significant risk factors for MDR Gram-negative infection (p <0.05) included age at admission ≥7 days, late-onset sepsis, bag-mask ventilation or re-intubation, blood transfusion, parenteral nutrition, umbilical or central line catheterization, invasive mechanical ventilation ≥7 days, use of vasopressors, and exposure to ≥2 antibiotics or antibiotic regimen changes during treatment. Conclusion: Gram-negative neonatal infections, particularly those caused by Klebsiella pneumoniae, are common and mainly associated with late-onset sepsis. Respiratory symptoms predominate, often accompanied by hematologic, biochemical, and coagulation abnormalities. Early identification and close monitoring of high-risk neonates, adherence to aseptic techniques, effective infection control, and rational antibiotic use are essential to improve outcomes and reduce mortality.